Oil Price Density Forecasts: Exploring the Linkages with Stock Markets - Marco J. Lombardi; Francesco Ravazzolo (Norges Bank, 2012)
In the recent years several commentators hinted at an increase of the correlation between equity and commodity prices, and blamed investment in commodity-related products for this. First, this paper investigates such claims by looking at various measures of correlation. Next, we assess to what extent correlations between oil and equity prices can be exploited for asset allocation. We develop a time-varying Bayesian Dynamic Conditional Correlation model for volatilities and correlations and find that joint modelling of oil and equity prices produces more accurate point and density forecasts for oil which lead to substantial benefits in portfolio wealth.
hdl:11250/2496812
Keywords: C11; C15; C53; E17; G17; 330; Bayesian DCC; Bayesian dynamic conditional correlation; oil price; stock price; density forecasting; correlation